PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PERAWATAN DIMEDIASI OLEH KESUKAAN MEREK DAN NIAT - Ayuk Wandirah; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of brand equity on skin care decision. Consumer’s purchace decision has come factors. The factors are brand equity, brand preference and purchase intention. The high brand equity affects the purchase decision. The data collect by using questionnaires for the Larissa Aesthetic Center customers in Surakarta with cluster. The sample collection was taken from 200 respondents. This analysis uses Structural Equation Modelling (SEM and logistic regress analysis. The result of the sudy shows that brand equity give the possitive effect of brand preference and purchase intention. Brand preference give that possitive effect of purchase intention and skin care decision. Purchase intention give the possitive effect of skin care decision